Physicochemical studies on the inhibitive properties of a 1,2,4-triazole Schiff’s base, HMATD, on the corrosion of mild steel in hydrochloric acid - P. Rugmini Ammal; M. Prajila; Abraham Joseph (Egyptian Journal of Petroleum)
The efficiency of 4-(4-hydroxy-3-methoxy benzyledene amino)-4-H-1,2,4-triazole-3, 5-dimethanol, HMATD, as corrosion inhibitor for mild steel in 0.5 M HCl has been determined by weight loss measurements and electro analytical methods. The influence of various parameters such as temperature, inhibitor concentration on the efficiency has been studied. The electrochemical impedance spectroscopic measurements revealed the inhibition action of HMATD by reducing the charge transfer through metal solution interface. Polarization curves indicate the mixed type behaviour of HMATD. The inhibitor molecule functions by blocking the active sites on metal surface by adsorption and which obeys the Langmuir adsorption isotherm. Various kinetic and thermodynamic parameters have also been calculated. Keywords: Mild steel, EIS, Activation energy, Adsorption isotherm, SEM